Efficacy of Justicia pectoralis Jacq. (Acanthaceae) in the treatment of individuals with hypertension: double-blind, placebo-controlled clinical trial - Chaves, Lucas (2024)
Ethnopharmacological relevance. Justicia pectoralis Jacq. (fresh cut, Acanthaceae) is medicinal plant traditionally used for respiratory diseases, anxiety, and hypertension. Aim of the study. To assess the antihypertensive efficacy of J. pectoralis in hypertensive adults in a randomized, double-blind, and placebo-controlled clinical trial. Patients and methods. Hypertensive patients on medication were eligible for the study and underwent the Ambulatory Blood Pressure Monitoring (ABPM) exam. Those who had a mean daytime systolic blood pressure (SBPd) ≥= 120 mm Hg at the baseline measurement (T0) were included and randomly allocated into two groups to receive J. pectoralis tincture or placebo (40 drops, twice a day). After 60 days of treatment, a new ABPM was performed, being considered the post-treatment measurement (T60). The mean differences of blood pressure measurements (systolic and diastolic) for all ABPM periods (daytime, nighttime and 24-hour) before and after treatment were calculated and presented with the respective confidence interval (95%CI). The primary outcome was the mean difference in 24-hour systolic blood pressure (24-hour SBP). Results. J. pectoralis tincture, when compared to placebo, after 60 days of treatment, promoted an average reduction in 24h SBP of -5.80 mm Hg (95%CI -0.4, -11.21, p=0.03). Conclusion. J. pectoralis exhibited antihypertensive activity in hypertensive adults, confirming the ethnopharmacological use of this species.